2023
DOI: 10.1021/acssuschemeng.2c04521
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Transformation of Ethylene Glycol for Selective Hydrogen Gas Production in Water

Abstract: We developed an efficient process for producing hydrogen gas from aqueous ethylene glycol (EG) at 90−160 °C over a ruthenium catalyst. We achieved a high yield of hydrogen gas (up to 3.0 n(H 2 )/n(EG)) and formic acid (85% yield) from ethylene glycol in aqueous alkaline medium at 110 °C, where the role of reaction temperature and base concentration was found to be critical in achieving a high yield of H 2 . The chemical and morphological properties of the synthesized ruthenium catalyst were established using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Liu et al 12 revealed that Pd and Au loaded on Ni(OH) 2 can also realize EG-to-GA at high current densities with high selectivity. Kumar et al 13 reported that a Ru catalyst can convert EG to formate with high selectivity and Faradaic efficiency. Nevertheless, the practical implementation of these noble-metal catalysts is strongly limited by their high cost and low reserves.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 12 revealed that Pd and Au loaded on Ni(OH) 2 can also realize EG-to-GA at high current densities with high selectivity. Kumar et al 13 reported that a Ru catalyst can convert EG to formate with high selectivity and Faradaic efficiency. Nevertheless, the practical implementation of these noble-metal catalysts is strongly limited by their high cost and low reserves.…”
Section: Introductionmentioning
confidence: 99%
“…Although Ru 3d 3/2 displays a significant overlap with the C 1s peak at 284.9 eV, the binding energy of Ru 3d 5/2 at 281.0 eV is consistent with the presence of Ru in its metallic [Ru(0)] state (Figure S17 of the Supporting Information). 29,46,47 The observed peaks at 282.2 eV (Ru 3d 5/2 ) and 465.8 eV (Ru 3p 3/2 ), suggesting the presence of an oxide layer, presumably formed as a result of exposure of the catalyst to air during XPS sample preparation (Figure 3 and Figures S17 and S18 of the Supporting Information). Advantageously, the in-Ru catalyst displayed high stability during a long-term recyclability experiment for hydrogen production from methanol during 10 consecutive catalytic runs of both 3 and 10 h cycles (Figure 4).…”
mentioning
confidence: 99%
“…Powder X-ray diffraction (P-XRD) analysis of the in -Ru catalyst, acquired after the catalytic reaction, revealed the presence of a broad peak in the 30–45° range, and an analogous pattern was also observed for the recovered catalyst ( sp -Ru), suggesting the high robustness of the catalyst (Figure ). , Transmission electron microscopy (TEM) imaging provides conclusive evidence of the homogeneous dispersion of ruthenium nanoparticles for in -Ru and sp -Ru catalysts, each exhibiting an average particle size of ca. 1.6 nm, suggesting no significant alteration in the recovered catalyst ( sp -Ru) (Figure and Figures S14 and S15 of the Supporting Information).…”
mentioning
confidence: 99%
“…Various attempts have been devoted on heterogeneous catalysts for the transformation of ethylene glycol for hydrogen production, either through high-temperature steam reforming or via aqueous phase reforming (APR) over supported metal catalysts 19–23 or metal-free graphene-based catalysts. 24 However, many of these strategies operate at high reaction temperatures, requiring complex reaction setups, and a loss of selectivity is observed.…”
mentioning
confidence: 99%
“…6,7 Although the utilization of ethylene glycol for the synthesis of several value-added chemicals, such as acids, [8][9][10][11] amides, 12 polyethyleneimine, 13 oligoester, 14,15 and N-heteroarenes 16 by dehydrogenative coupling has grown as a potential methodology for upgrading this feedstock nonetheless to maximize its utility, reforming ethylene glycol to produce hydrogen is of great concern. 17,18 Various attempts have been devoted on heterogeneous catalysts for the transformation of ethylene glycol for hydrogen production, either through high-temperature steam reforming or via aqueous phase reforming (APR) over supported metal catalysts [19][20][21][22][23] or metal-free graphene-based catalysts. 24 However, many of these strategies operate at high reaction temperatures, requiring complex reaction setups, and a loss of selectivity is observed.…”
mentioning
confidence: 99%